Oral Symptom Intensity, Health-Related Quality of Life, and Correlative Salivary Cytokines in Adult Survivors of Hematopoietic Stem Cell Transplantation with Oral Chronic Graft-versus-Host Disease - Fall-Dickson, Jane M.; Mitchell, Sandra A.; Marden, Susan; Ramsay, Edward S.; Guadagnini, Jean-Pierre; Wu, Tianxia; St. John, Lena; Pavletic, Steven Z. (Biology of blood and marrow transplantation, 2010)
Oral chronic graft-versus-host disease (cGVHD) is a frequent, clinically significant sequela of allogeneic hematopoietic stem cell transplantation (HSCT). This study was designed to elucidate relationships among clinical characteristics of oral cGVHD and related oral pain and oral dryness, salivary proinflammatory cytokine interleukin (IL)-6 and IL-1α concentrations, and health-related quality of life (HRQL). An understanding of the characteristics and correlates of oral cGVHD manifestations and related symptoms, such as oral dryness, is fundamental to the development of therapeutic interventions. Oral cGVHD severity was assessed with the Oral Mucositis Rating Scale (OMRS). Oral pain and perceived intensity of oral dryness were self-reported via a visual analog scale and a numeric rating scale, respectively. HRQL was assessed with the Functional Assessment of Cancer Therapy-General (FACT-G). Salivary IL-1α and IL-6 concentrations were measured by enzyme-linked immunosorbent assay. All 42 adult subjects (59% males) had clinician-assessed oral cGVHD by the OMRS scale (mean score, 18.38 ± 12.99; range, 2-46). Oral dryness (in 43% of subjects; mean OMRS score, 2.56 ± 3.45; range, 0-10) was more prevalent than oral pain (8%; mean score, 0.13 ± 0.47). Salivary IL-6 was associated with oral cGVHD severity ( r = 0.49; P < .01), oral ulceration ( r = 0.38; P = .04), and erythema ( r = 0.63; P < .01). FACT-G total score and physical and emotional well-being subscale scores were meaningfully lower than U.S. population normative values. Participants with more severe oral cGVHD manifestations had significantly inferior social/family well being ( r = -0.49; P < .01). Oral dryness was associated with higher salivary IL-1α ( r = 0.41; P = .04) and, controlling for cGVHD severity, with lower HRQL ( r = -0.41; P = .03). Subjects with moderate to severe oral dryness tended to report the poorest overall HRQL. This study provides preliminary evidence of the relationship between oral dryness and HRQL, the contribution of oral cGVHD to inferior HRQL, and the association between IL-6 and oral cGVHD severity, ulceration, and erythema. The high prevalence of oral dryness and its relationship to HRQL in a sample of subjects with oral cGVHD underscores the importance of improving our evaluation and management of this symptom in long-term survivors of allogeneic HSCT. The positive associations between IL-6 and oral cGVHD severity and erythema, as well as the positive trend with oral ulceration, warrant further exploration of this cytokine as a potential biomarker of active oral cGVHD.